2000
DOI: 10.1042/0264-6021:3470543
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis or senescence-like growth arrest: influence of cell-cycle position, p53, p21 and bax in H2O2 response of normal human fibroblasts

Abstract: Early-passage human diploid fibroblasts (HDFs) undergo senescence-like growth arrest in response to sublethal concentrations of H(2)O(2) [Chen and Ames (1994) Proc. Natl. Acad. Sci. USA. 95, 4130-4134]. We determine here whether H(2)O(2) can cause apoptosis in HDFs and the molecular changes that differ between apoptosis and senescence-like growth arrest. When exponentially growing early-passage IMR-90 cells were treated for 2 h with 50-200 microM (or 0.25-1 pmol/cell) H(2)O(2), a fraction of cells detached at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(70 citation statements)
references
References 51 publications
0
70
0
Order By: Relevance
“…Liver regeneration also might be affected by ROS via indirect or direct effects [29][30][31][32][33][34][35]. As an indirect effect, it has been reported that stellate cells activated via the ROS system produce excessive transforming growth factor beta (TGF-b), a potent inhibitory cytokine for liver regeneration [29,30].…”
Section: Discussionmentioning
confidence: 98%
“…Liver regeneration also might be affected by ROS via indirect or direct effects [29][30][31][32][33][34][35]. As an indirect effect, it has been reported that stellate cells activated via the ROS system produce excessive transforming growth factor beta (TGF-b), a potent inhibitory cytokine for liver regeneration [29,30].…”
Section: Discussionmentioning
confidence: 98%
“…It was found that Bcl-2 levels are positively regulated by the transcription factor CREB (cAMP responsive element binding protein). A reduction in phospho-CREB (Ser-133) levels was observed in young but not in senescent HDFs in response to apoptotic stimuli [53,55,77,82]. The phosphatase PP2A was responsible for inactivation of CREB in young HDFs.…”
Section: The Bcl-2 Family In Senescencementioning
confidence: 94%
“…These findings were subsequently extended to primary human fibroblasts undergoing replicative-as well as oxidative stress-induced senescence [81,82]. Furthermore, up-regulation of Bcl-2 in senescent cells proved to be a general mechanism of resistance to a variety of apoptotic stimuli [77,81,82]. It was found that Bcl-2 levels are positively regulated by the transcription factor CREB (cAMP responsive element binding protein).…”
Section: The Bcl-2 Family In Senescencementioning
confidence: 96%
See 1 more Smart Citation
“…For example, low dose of the DNA-damaging agent doxorubicin leads to cellular senescence, while high dose will induce apoptosis in rat cardiomyocytes (Spallarossa et al 2009, Altieri et al 2012. Low dose of H 2 O 2 also induces cellular senescence in human lung and skin fibroblasts, while high dose promotes apoptosis in these cells (Chen & Ames 1994, Chen et al 2000. Some DNAdamaging agents, such as busulfan, preferentially cause human lung fibroblasts to undergo cellular senescence instead of apoptosis (Probin et al 2006).…”
Section: Cellular Senescence and Ovarian Agingmentioning
confidence: 99%